Advertising Progress - Laird, Pamela Walker (Johns Hopkins University Press, 2020)
Selected by Choice Magazine as an Outstanding Academic TitleOriginally published in 1998. Drawing on both documentary and pictorial evidence, Pamela Walker Laird explores the modernization of American advertising to 1920. She links its rise and transformation to changes that affected American society and business alike, including the rise of professional specialization and the communications revolution that new technologies made possible. Laird finds a fundamental shift in the kinds of people who created advertisements and their relationships to the firms that advertised. Advertising evolved from the work of informing customers (telling people what manufacturers had to sell) to creating consumers (persuading people that they needed to buy). Through this story, Laird shows how and why—in the intense competitions for both markets and cultural authority—the creators of advertisements laid claim to "progress" and used it to legitimate their places in American business and culture.